Severity of respiratory signs and symptoms and virus profiles in Japanese children with acute respiratory illness. (December 2013) - Miyaji, Yumiko; Kobayashi, Miho; Sugai, Kazuko; Tsukagoshi, Hiroyuki; Niwa, Shoichi; Fujitsuka‐Nozawa, Asako; Noda, Masahiro; Kozawa, Kunihisa; Yamazaki, Fusae; Mori, Masaaki; Yokota, Shumpei; Kimura, Hirokazu
ABSTRACT Associations between the severity of respiratory signs and symptoms and the respiratory viruses identified in 214 Japanese children with acute respiratory illness (ARI) enrolled between January and December 2012 were studied. Respiratory rate, wheezing, cyanosis, and the use of accessory muscles were used as indices of respiratory severity and phylogenetic analysis of the viruses identified in these children was performed. Respiratory viruses such as respiratory syncytial virus (RSV), human rhinovirus (HRV), human parainfluenza virus (HPIV), and human metapneumovirus (HMPV) were prevalent, being detected in approximately 70% of the patients (151/214 patients). Co‐detection of viruses occurred in about 9% of patients. RSV was identified more frequently in cases scored as moderate/severe than in those scored as mild (P < 0.05). Severity scores of patients with RSV were significantly higher than those of cases with HPIV. Moreover, severity scores in patients with mild disease and co‐detections were higher than in those in whom only HPIV or adenovirus was detected. Phylogenetic analysis showed that many genotypes of HRV‐A and ‐C with wide genetic divergence were associated with acute respiratory illness (ARI). On the other hand, only a limited number of genotypes of RSV were associated with ARI. HPIV and HMPV were associated with ARI at similar frequencies. These results suggest that different respiratory viruses with unique genetic characteristics can be found in patients with mild to severe ARI.